Functional plasticity of benthic macroinvertebrates: implications for trophic dynamics in acid streams - Dangles, Olivier (Canadian journal of fisheries and aquatic sciences, 2002)
Functional plasticity of benthic macroinvertebrates was investigated over one year in four acid streams in the Vosges Mountains (northeastern France). The trophic position of macroinvertebrate species within the benthic food web was determined using gut content analyses. Diet analyses revealed that only 2436% of biomass of putative shredders consumed leaf fragments, whereas up to 44% consumed benthic algae and bryophytes. Although most Nemouromorpha stoneflies were generalist consumers, several other taxa (e.g., Brachyptera seticornis, Chaetopterygopsis maclachlani) specialised on benthic algae and bryophytes. Our study showed that acid streams unexpectedly had very few specialised leaf-shredding species (e.g., Chaetopteryx villosa) that could explain the slow leaf detritus processing rates observed in these systems. Primary producers appear to be an alternative resource for shredders, playing an important role in supporting food webs in forested acid streams. The food web built in this study suggests that overlooking species-specific functional plasticity of invertebrates may result in a misconception of invertebrate community structure in acid streams.